Detection of specific antibodies to HCV-ARF/CORE+1 protein in patients treated with pegylated interferon plus ribavirin - Karamitros, T; Kakkanas, A; Katsoulidou, A; Sypsa, V; Dalagiorgou, G; Mavromara, P; Hatzakis, A (Wiley, 2011)
Hepatitis C virus (HCV) infection is a major cause for chronic liver disease and hepatocellular carcinoma. The HCV-ARF/core+1 protein is an alternative product of HCV core-encoding sequence of unknown biological function. Highly purified HCV core and ARF/core+1 recombinant proteins from HCV genotype 1a and HCV-ARF/core+1 recombinant protein from HCV genotype 3a were expressed in Escherichia coli. Using an enzyme-linked immunosorbent assay, we assessed the prevalence of anti-ARF/core+1 antibodies in 90 chronic hepatitis C patients infected with HCV genotypes 1a/1b or 3a, treated with pegylated interferon (Peg-IFN-a-2a) plus ribavirin. Samples derived from 92 healthy blood donors were used as negative controls. All HCV-RNA-positive serum samples reacted with core 1a antigen, while 15 (37.5%) of 40 and 14 (28%) of 50 patients infected with HCV-1a/1b and HCV-3a, respectively, were found to have anti-ARF/core+1 antibodies into their serum before treatment initiation. These antibodies were persistently present during treatment follow-up and linked to elevated levels of HCV-RNA at baseline.